1999
DOI: 10.1257/aer.89.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Do Domestic Firms Benefit from Direct Foreign Investment? Evidence from Venezuela

Abstract: Governments often promote inward foreign investment to encourage technology 'spillovers' from foreign to domestic firms. Using panel data on Venezuelan plants, the authors find that foreign equity participation is positively correlated with plant productivity (the 'own-plant' effect), but this relationship is only robust for small enterprises. They then test for spillovers from joint ventures to plants with no foreign investment. Foreign investment negatively affects the productivity of domestically owned plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

105
2,121
10
50

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,838 publications
(2,286 citation statements)
references
References 10 publications
105
2,121
10
50
Order By: Relevance
“…As Aitken and Harrison (1999) argue, multinationals producing at lower marginal costs than host country firms have an incentive to increase output and attract demand away from these firms. This will cause host country rivals to cut production which, if they face fixed costs of production, will raise their average cost.…”
Section: Productivity Spilloversmentioning
confidence: 99%
“…As Aitken and Harrison (1999) argue, multinationals producing at lower marginal costs than host country firms have an incentive to increase output and attract demand away from these firms. This will cause host country rivals to cut production which, if they face fixed costs of production, will raise their average cost.…”
Section: Productivity Spilloversmentioning
confidence: 99%
“…3 See Blomström and Kokko (1998) for a literature review on the externalities associated with FDI and Aitken and Harrison (1999) for firm-level evidence of the positive impact of FDI on foreign-owned operations.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have so far produced mixed results. Some studies showed evidence of positive technology spillovers from FDI to local firms, while other studies found that FDI negatively affects the productivity of local firms (see, for instance, Caves, 1974;Globerman, 1979;Kokko;Blomstrom and Wolff, 1996;Aitken and Harrison, 1999;Djankov and Hoekman, 2000;Kathuria, 2000;Chung, 2001;Chuang, Mitchell and Yeung, 2003;Javorcik, 2004;Wei and Liu 2006;Tian 2007;Buckley, Clegg and Wang 2007). 2 Interestingly enough, both sides in the debate have looked at the issue almost exclusively from the perspective of local firms that receive the spillovers rather than the perspective of TNCs that generate the spillovers.…”
mentioning
confidence: 99%